CINCINNATA-Like TCP Transcription Factors in Cell Growth – An Expanding Portfolio - Rath, Monalisha; Challa, Krishna Reddy; Sarvepalli, Kavitha; Nath, Utpal (Frontiers in Plant Science, 2022)
Post-mitotic cell growth is a key process in plant growth and development. Cell expansion drives major growth during morphogenesis and is influenced by both endogenous factors and environmental stimuli. Isotropic cell growth increases organ size whereas directional growth regulates shape. While much is known about the mechanisms that increase cellular turgor and cell-wall biomass during expansion, the genetic factors that regulate these processes are less studied. In the past quarter of a century, the role of the CINCINNATA-like TCP (CIN-TCP) transcription factors has been well documented in regulating diverse aspects of plant growth and development including flower asymmetry, plant architecture, leaf morphogenesis and plant maturation. The molecular activity of the CIN-TCP proteins common to these biological processes has been identified as their ability to suppress cell proliferation. However, reports on their role in regulating post-mitotic cell growth have been scanty, partly because of functional redundancy among them. In addition, it is difficult to tease out the effect of gene activity on cell division and expansion since these two processes are linked by compensation, a phenomenon where perturbation in proliferation is compensated by an opposite effect on cell growth to keep the final organ size relatively unaltered. Despite these technical limitations, recent genetic and growth kinematic studies have shown a distinct role of CIN-TCPs in promoting cellular growth in cotyledons and hypocotyls, the embryonic organs that grow solely by cell expansion. In this review, we highlight these recent advances in our understanding of how CIN-TCPs promote cell growth.